Analisis Visual Artefak Budaya Makuta Binokasih Sang Hyang Pake - Oetari, Jeng; Ciptandi, Fajar; Rosandini, Morinta (Telkom University, 2023)
The Binokasih Crown is a Sundanese cultural heritage object stored in the Prabu Geusan Ulun Museum in Sumedang Regency as a symbol of the coronaton of a king in the contnuaton of power. The Binokasih Crown is designated as a Kasumedangan ornament and its visual is also used in the Sumedang Puseur Budaya Sunda or SPBS logo. In the use of the crown’s visual, there are diferences in history and no comprehensive descripton. Through the eforts of Sumedang Puseur Budaya Sunda in reconstructng culture and the need to identfy artfacts through cultural values, it is necessary to study the Binokasih Crown as an icon of Sumedang Regency through Sundanese cultural values in an efort to preserve Sundanese culture in Sumedang. The method used in this research is a qualitatve method with data collecton through feld observaton, deep interviews, document studies, and documentaton. The data analysis technique on cultural values uses Sundanese Cosmology and visual analysis uses morphological aesthetcs with descriptve, analytcal, interpretatve, and evaluatve stages. The purpose of this research is to explore the tangible and intangible aspects of the Makuta Binokasih as a cultural artfact. This is done in order to preserve Sundanese cultural heritage, and to provide a clear foundaton for the development of products based on the artfact.